Pengaruh Kompetensi terhadap Kinerja Karyawan: Tinjauan Literatur Sistematis - Ibnu Ngabas; Bambang Setiarto; Dani Rizana (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Employee competency is a strategic factor in improving organizational performance. Rapid changes in the business environment, technological advancements, and increasing demands for professionalism require organizations to ensure that their human resources possess adequate knowledge, skills, abilities, and work attitudes. This study aims to analyze the influence of employee competency on performance using a Systematic Literature Review (SLR) approach based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method. Relevant research articles were identified through a systematic process consisting of identification, screening, eligibility assessment, and inclusion according to predetermined criteria. The selected studies were then synthesized to evaluate the relationship between competency and employee performance across various organizational contexts. The findings consistently indicate that employee competency has a positive and significant influence on performance improvement. Competency, which encompasses knowledge, technical and interpersonal skills, professional attitudes, and individual characteristics, contributes to enhancing work effectiveness, productivity, service quality, innovation, and the achievement of organizational objectives. Furthermore, organizations that continuously invest in competency development through education, training, and continuous learning programs tend to achieve higher employee performance and stronger organizational competitiveness. This study provides comprehensive evidence that competency development is a fundamental strategy for improving organizational performance and offers practical implications for managers and policymakers in designing sustainable human resource development programs.